A new QoS aware and energy efficient opportunistic routing protocol for wireless sensor networks. Issue 1 (2nd January 2018) - Tiab, Amal; Bouallouche-Medjkoune, Louiza; Boulfekhar, Samra
Abstract: Energy efficiency and Quality of Service (QoS) providing are known to be critical design concerns in routing protocols for Wireless Sensor Networks (WSNs). Recent studies, demonstrate that Opportunistic Routing (OR) can greatly improve the performance of WSNs by exploiting the broadcast nature of the wireless medium. In this paper, we propose a new QoS aware and Energy efficient Opportunistic Routing protocol (QEOR) to efficiently routing data under QoS and energy constraints for WSNs. QEOR uses a new multi-metric QoS based candidate selection method in order to accurately select and prioritise the candidate forwarders. The selection is focused on a QoS function that takes into consideration the reliabilty of buffers and links, while the prioritisation is established according to transmission delays. To achieve an obvious improvement on the energy consumption, QEOR uses an energy efficient coordination method and an implicit ACKnowledgement scheme for collision and redundancy avoidance. Simulation results show that QEOR provides best performances as compared to other OR protocols. Graphical Abstract: